2020
DOI: 10.1002/anie.202002147
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Strategy to Eliminate Hexosylation Bias in the Relative Quantification of N‐Glycosylation in Biopharmaceuticals

Abstract: N‐glycosylation may affect the safety and efficacy of biopharmaceuticals and is thus monitored during manufacturing. Mass spectrometry of the intact protein is increasingly used to reveal co‐existing glycosylation variants. However, quantification of N‐glycoforms via this approach may be biased by single hexose residues as introduced by glycation or O‐glycosylation. Herein, we describe a simple strategy to reveal actual N‐glycoform abundances of therapeutic antibodies, involving experimental determination of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…Denosumab was earlier reported to be glycated [38], but in our case the spectra lacked any signs of glycation, suggesting a glycation level below our NMR detection limit, or a modification with another reducing sugar other than glucose. However, it is also possible, that the glycation was lost during the sample preparation due to its reversibility [28].…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Denosumab was earlier reported to be glycated [38], but in our case the spectra lacked any signs of glycation, suggesting a glycation level below our NMR detection limit, or a modification with another reducing sugar other than glucose. However, it is also possible, that the glycation was lost during the sample preparation due to its reversibility [28].…”
Section: Discussioncontrasting
confidence: 57%
“…Despite the high complexity of the 1 H- 13 C HSQC spectrum and many correlations of the containing glycans, the typical regions for C5-H5 (71.8/4.01 ppm), C6-H6 (66.7 /4.01 ppm) and C6-H6′ (66.7 /3.76 ppm) were empty. Denosumab was described to be glycated [38], but from our NMR data (see Fig. 5C), we concluded that either the glycation level was below the detection limit, or another form of modification was present, different from glycation with glucose.…”
Section: Glycation In Natural Proteinsmentioning
confidence: 74%
See 2 more Smart Citations
“…Non-enzymatic attachment of a hexose to a backbone residue results in a mass shift identical to that for a mannose or antennal galactose extension of an N -glycan, making it indiscernible on the intact-protein level. Recently, Esser-Skala et al , presented a method to assign possible PTM compositions and to eliminate hexosylation bias in the analysis of N-glycosylation patterns by native MS. When measuring the antibody in its N -deglycosylated form, satellite peaks at intervals of 162 Da indicated the presence of nonspecifically glycated isoforms.…”
Section: Proteoform Profiling By High-resolution Native Msmentioning
confidence: 99%